Unintended Consequences of Agricultural Participation in Voluntary Carbon Markets: Their Nature and Avoidance. (17th July 2021) - Wang, Minglu; McCarl, Bruce; Wei, Hanlin; Shiva, Layla
Abstract : Greenhouse gas (GHG) trading markets have been widely discussed for climate change mitigation. However in implementation coverage has not been universal. Agriculture, despite being the source of nearly 25% of net emissions, has not commonly been capped. But it has been mentioned as voluntary source of net emission offsets. Such offsets could arise from action reducing GHG emissions, enhancing sequestration, or producing feedstocks for low emitting bioenergy replacements for fossil based energy. This could be harnessed by setting up voluntary carbon markets that producers could join at their discretion. However, such a scheme could have unintended consequences. We conduct theoretical and empirical analyses of a voluntary "carbon" market examining both intended and unintended effects. We find certain participation rules can stimulate rebound effects from emitters and suppress participation from sequestration and bioenergy producing entities. To overcome this we develop and simulate offset participation limitations that could preclude unintended consequences.